Proposal for Introducing a Digital Aesthetic Dentistry Course in Undergraduate Program: Contents and Ways of Administration - Francesca Zotti; Annalisa Cominziolli; Davide Pappalardo; Luca Rosolin; Dario Bertossi; Nicoletta Zerman (MDPI AG, 2022)
Background: Nowadays, digital dentistry is a fundamental skill that dentists need to acquire at this time. The digital workflow has gained acceptance and is widely used in most disciplines of dentistry. For this reason, it might be advisable to include this content in the undergraduate curriculum. The aim of this work was to create a course in digital aesthetic dentistry and evaluate its effectiveness. Methods: Dental students at the University of Verona (from third to sixth year) participated in a 2-h course on photography, digital aesthetic analysis, and digitally planned rehabilitations. Students were randomly divided into two groups, the first group attending the course with video tutorials and the second group attending the traditional class with slides. The students' ability to perform digital aesthetic analysis and rehabilitation was tested. In addition, a questionnaire was completed to determine student satisfaction with the course and method of delivery. Statistical analysis was performed. Results: The course was highly appreciated, especially by the students who received the video tutorials. Good results were obtained in the performance of digital analysis and rehabilitation, which were better in the first group. Conclusions: Digital aesthetic dentistry was a success in terms of newly acquired skills. From this point of view, the proposal of a course on this subject in the undergraduate curriculum deserves a close evaluation. The video tutorial method seems to be a good way to teach operative digital procedures.